2001
DOI: 10.1002/1521-186x(200102)22:2<106::aid-bem1013>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Modification of electrokinetic properties of nuclei in human buccal epithelial cells by electric fields

Abstract: The influence of an alternating (50 Hz) electric field (5--110 V/cm) on the state of human buccal epithelium cells was studied by the methods of intracellular microelectrophoresis, heterochromatin staining with orcein, and indigo carmine staining for viability and membrane integrity evaluations. Electric field exposure induced an increase in electrophoretic mobility of cell nuclei, decreased numbers of heterochromatin granules near the inner membrane of cell nucleus, and induced cell membrane damage; but cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In recent years, the findings concerning the MF-dependence of the FL cell and nuclear volumes 4,83 were supported by those regarding the MF-dependence of the electrokinetic properties of nuclei in human buccal epithelial cells. 84 Other studies of general character were devoted to the analysis of the socalled "electromagnetic man" vs. the magnetic resonance tomography 85 and of the effect of MFs on synchronization of mammalian cell permeabilization vs. the MF-dependence of gene delivery. 86 From a methodological point of view, attempts were made to employ programmmed chronopotentiometry as a tool to study electroporation and resealing of pores in bilayer lipid membranes, 87 while an EU-wide initiative to characterize the biological effects of EMF on human and mouse cell lines by gene expression profiling was taken.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the findings concerning the MF-dependence of the FL cell and nuclear volumes 4,83 were supported by those regarding the MF-dependence of the electrokinetic properties of nuclei in human buccal epithelial cells. 84 Other studies of general character were devoted to the analysis of the socalled "electromagnetic man" vs. the magnetic resonance tomography 85 and of the effect of MFs on synchronization of mammalian cell permeabilization vs. the MF-dependence of gene delivery. 86 From a methodological point of view, attempts were made to employ programmmed chronopotentiometry as a tool to study electroporation and resealing of pores in bilayer lipid membranes, 87 while an EU-wide initiative to characterize the biological effects of EMF on human and mouse cell lines by gene expression profiling was taken.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that age-related differences in ENN between donors are connected with changes of cell nucleus charges, but not with cell membrane permeabilities [10,11]. Catabolic hormones, such as epinephrine, norepinephrine, hydrocortisone caused a significant ENN decrease [12].…”
Section: Introductionmentioning
confidence: 99%